2019
DOI: 10.3390/ma12030372
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed UV Laser Processing of Carbosilane and Silazane Polymers

Abstract: Freestanding SiCNO ceramic pieces with sub-mm features were produced by laser crosslinking of carbosilane and silazane polymer precursors followed by pyrolysis in inert atmosphere. Three different pulsed UV laser systems were investigated, and the influence of laser wavelength, operating power and scanning speed were all found to be important. Different photoinitiators were tested for the two lasers operating at 355 nm, while for the 266 nm laser, crosslinking occurred also without photoinitiator. Pre-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…39 This exotherm can be attributed to the burning of hydrogen and small-molecular-weight hydrocarbons. 40 However, the intensity of this broad peak is significantly reduced in the DSC curve of Ppy NF-BF, which instead shows a broad and weak exothermic wave (from 120 to 460 °C) with a constantly increasing endothermic tail (started at 460 °C). The substantial weakening of the exothermic peak indicates that the thermal decomposition of Ppy NFs is impeded by the PEG nanocoating, and the Ppy NFs may go through a pyrolysis process instead of decomposition.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…39 This exotherm can be attributed to the burning of hydrogen and small-molecular-weight hydrocarbons. 40 However, the intensity of this broad peak is significantly reduced in the DSC curve of Ppy NF-BF, which instead shows a broad and weak exothermic wave (from 120 to 460 °C) with a constantly increasing endothermic tail (started at 460 °C). The substantial weakening of the exothermic peak indicates that the thermal decomposition of Ppy NFs is impeded by the PEG nanocoating, and the Ppy NFs may go through a pyrolysis process instead of decomposition.…”
Section: Resultsmentioning
confidence: 97%
“…The differential scanning calorimetry (DSC) curve of the Ppy NFs shows a broad exothermic peak centered at 350 °C, corresponding to the thermal decomposition of Ppy (Figure c) . This exotherm can be attributed to the burning of hydrogen and small-molecular-weight hydrocarbons …”
Section: Resultsmentioning
confidence: 99%
“…In general, the operational optical bandwidth of LCOS is limited from the visible (VIS) to the near-infrared (NIR) range, owing to an ultraviolet absorption of the constitutional materials; although some effective studies for liquid crystal devices under ultraviolet (UV) light have been reported [8][9][10][11]. However, there are so many interesting applications in the UV range [12][13][14], such as 3D printing, integrated circuit (IC) laser trimming, printed circuit board (PCB) cutting and maskless exposure. In this paper, we report a UV durable LCOS technology for LCOS based UV laser processing.…”
Section: Introductionmentioning
confidence: 99%